Comprehensive Nursing Care in a Neonatal Asphyxia with Hypoxic Ischemic Encephalopathy and Sepsis Complications: A Case Report - Sugiharto, Firman; Khoirunnisa, Khoirunnisa; Hendrawati, Sri; Alya, Fania Putri (Padjadjaran Acute Care Nursing Journal, 2025)
Background: Asphyxia is one of the highest causes of neonatal mortality in the world. Delayed treatment of asphyxia can have an impact on permanent organ failure and neurological disability in neonates such as cerebral palsy, hyperactivity, and epilepsy.Aim: This study aimed to describe nursing care for neonates with asphyxia neonatorum.Case Description: A boy named H (By. H), 22 day old was transferred from the neonatal intensive care unit (NICU) with a diagnosis of severe asphyxia with complications of HIE and sepsis. At the time of assessment, the level of consciousness compos mentis, general condition was weak, often restless, short of breath, there was lobed breathing, intercostal retractions, stridor, secret in the mouth, rhonchi in both lung fields. Vital signs obtained HR: 150 x/minute, RR: 50 x/minute, body temperature: 36.60C, SpO2: 96%. The neonatus has good nutritional status and adequate hydration status, with positive fluid balance and no signs of fluid overload. Rest and sleep status of the neonatus is enough. The patient had a history of apnea, seizures, and post cooling therapy.Conclusion: The interventions and implementations carried out were monitoring vital signs, monitoring signs and symptoms of hypoxia, monitoring additional breath sounds, positioning the semi-fowler 30-450, changing position to prone position after breastfeeding, and nebulization with 3% NaCl 4 ml. After the intervention, the nursing problems in this case study had only been partially resolved. There is a need for further monitoring related to airway management which includes observation of vital signs and respiratory distress, continued nebulization with 4 ml of 3% NaCl, and monitor for signs of hypoxia.